Rancang Bangun Sistem Informasi Akademik Dengan Metode Knowledge Management Berbasis Website Madrasah Aliyah Hidayatusuban Semarang - Muhamad Sidik; Hendri Rasminto (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The development of information technology is currently increasingly rapid and diverse, supported by computer devices. Primarily in the field of information systems, information systems in related educational institutions are usually called academic information systems, for example student data, teacher data, class data, subject data, schedule data, grade data. Madrasah Aliyah Hidayatusuban Semarang is a school that conveys information through media, so that when conveying information it is not fast enough because the means of communication are lacking between the school, students and parents are not good at digesting academic information, to overcome the problem the author created an Academic Information System with a Knowledge Management method based on Web and PHP as programming languages ​​and use MySQL database. With the existence of a web-based information system with the Knowledge Management method, this can be a solution to solving the problems that exist at Madrasah Aliyah Hidayatusuban Semarang because web technology is easy and easy to access anywhere by parents and students, as well as teachers and employees can manage academics. offline (in a school environment) because the Knowledge Management method itself is a collection of information that is put together in one place and can provide knowledge to users effectively and efficiently in supporting activities